(untitled) (University of Khartoum Journal of Agricultural Sciences, 2023)
This laboratory and semi-field studies were designed toexplore the larvivorous potential of Gambusia affinis and ways this fishmight be employed in an ongoing Sennar state mosquito control program.The present experiments were conducted on G. affinis feeding patterns.The mean number of larvae consumed by G. affinis was 132 larvae during24 hours. Additionally, G. affinis had a tendency to feed on early instarsthan the late ones under both laboratory and semi-field conditions inSennar state. The percentages of larval consumption were 98% (±4),86.2% (±13.6), 77.4% (±7.3) and 63.6% (±32.5) for the 1st, 2nd, 3rd, and4th instars, respecti`vely. The percentage of larvae consumed of variedinstars was 87.4% (±21.8). Moreover, total consumption of the immaturestages of mosquito larvae can be achieved as the number of Anopheleslarvae consumed ranged between 46.7% and 100% (mean 72.68%±20.04) and of Culex larvae between 54.2% and 100% (mean 86.7%±20.27). This study suggests that G, affinis could be a useful tool in theongoing Sennar state vector control program. Further studies should beperformed to assess the ecology, seasonality and to be conducted underlarge scale